PENDAMPINGAN PENDIDIKAN NON FORMAL DIPOSDAYA MASJID JAMI’ AN-NUR DESA CLURING BANYUWANGI - Ahmad Izza Muttaqin; Riza Faishol (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2018)
Education can be a benchmark for the progress and quality of life of a nation, so that it can be said that the progress of a nation or state can be achieved by one of them through reform and the arrangement of good education.This community service is realized in the form of developing a mosque-based Family Empowerment Post (Posdaya). The mosque is an instrument of empowering people who have a very strategic role in improving the quality of society.Some program activities carried out in this service are as follows: a) Organize Tutoring (BIMBEL) at the Community Service Center b) Teaching / KBM at Darul Amin TPQ